Synthesis of Secondary Phosphine Oxides by Substitution at Phosphorus by Grignard Reagents - Tripolszky, Anna; Keglevich, Gyorgy (Letters in Organic Chemistry, 2018)
Secondary phosphine oxides (SPOs) are important starting materials in organophosphorus syntheses, and may be the ligands in transition metal complexes. SPOs are obtained from phosphorus trichloride via double substitution by a Grignard reagent followed by hydrolysis, or from dialkyl phosphites by reaction with two equivalents of a Grignard reagent. The preparation of SPOs with two different substituents is of special importance. This minireview gives useful hints for the synthesis of a variety of SPOs that are useful intermediates.
Keywords: secondary phosphine oxides